2022
DOI: 10.3390/ijerph19159573
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mental Disorders and the COVID-19 Pandemic—Course, Risk Factors, and Potential Consequences

Abstract: In this review the authors discuss that COVID-19 has already had a direct impact on the physical health of many people and that it appears to have put at risk the mental health of large populations. In this review, we also discuss the relationship between mental disorders and the SARS-CoV-2 infection. We convey the disorders’ risk factors and the more serious mental disorder consequences of COVID-19. People with mental health disorders could be more susceptible to the emotional responses brought on by the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 187 publications
0
10
0
2
Order By: Relevance
“…Besides, since SARS-CoV-2 presents neurotropic properties, some patients were also reported to present various neurological manifestations including conscious disturbance, acute cerebrovascular disease, confusion, or corticospinal tract signs [52,53]. Further, a relationship between the infection with SARS-CoV-2 and the onset of various mental disorders including depressive major disorder, bipolar disorder, schizophrenia, or dementia was reported [54]. The growing evidence also suggests a role of the SARS-CoV-2 infection in the onset of spontaneous psychosis even among individuals without any previous episodes or even psychiatric history.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, since SARS-CoV-2 presents neurotropic properties, some patients were also reported to present various neurological manifestations including conscious disturbance, acute cerebrovascular disease, confusion, or corticospinal tract signs [52,53]. Further, a relationship between the infection with SARS-CoV-2 and the onset of various mental disorders including depressive major disorder, bipolar disorder, schizophrenia, or dementia was reported [54]. The growing evidence also suggests a role of the SARS-CoV-2 infection in the onset of spontaneous psychosis even among individuals without any previous episodes or even psychiatric history.…”
Section: Discussionmentioning
confidence: 99%
“…The children who attend therapy are at high risk of being derailed from treatment and special education, and economically underprivileged children are prone to exploitation and abuse. Quarantined children are at great risk for developing mental health-related issues [102][103][104][105].…”
Section: Multisystem Inflammatory Syndrome In Children (Mismentioning
confidence: 99%
“…Wu et al 2009). Such elevated anxiety symptoms have been associated with poorer physical health (Sauer, Jungmann, and Witthöft 2020), life impairment across several domains (e.g., educational, occupational and interpersonal; Markiewicz-Gospodarek et al 2022), increased substance use (Zvolensky et al 2022) and higher rates of comorbidity with other mental health conditions (e.g., depression; Chen et al 2020). Some work has suggested that one useful and integrative perspective on emotional functioning in the pandemic pertains to coronavirus anxiety, which reflects physiologically based symptoms that are elicited by COVID-19related information and thoughts (e.g., 'I felt dizzy, lightheaded, or faint, when I read or listened to news about the Coronavirus'; S. Lee 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such elevated anxiety symptoms have been associated with poorer physical health (Sauer, Jungmann, and Witthöft 2020), life impairment across several domains (e.g., educational, occupational and interpersonal; Markiewicz‐Gospodarek et al. 2022), increased substance use (Zvolensky et al. 2022) and higher rates of comorbidity with other mental health conditions (e.g., depression; Chen et al.…”
Section: Introductionmentioning
confidence: 99%